2008
DOI: 10.1111/j.1528-1167.2008.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced serum level of THDOC, an anticonvulsant steroid, in women with perimenstrual catamenial epilepsy

Abstract: SUMMARYPurpose: Seizure exacerbation in catamenial epilepsy (CE) is associated with the decrease in progesterone secretion and increase in estradiol secretion during the premenstrual period. Moreover, experimental evidence suggests that tetrahydrodeoxycorticosterone (THDOC), a positive modulator of the type A receptor for γ -aminobutyric acid (GABA), and dehydroepiandrosterone sulfate (DHEAS), a negative modulator of this receptor, might play a crucial role in modulating seizure frequency during the menstrual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 52 publications
3
54
0
Order By: Relevance
“…During the menstrual cycle, circulating progesterone levels are low in the follicular phase, but rise in the midluteal phase for approximately 10 to 11 days before declining in the late luteal phase. Circulating AP levels parallel those of its parent progesterone (Tuveri et al, 2008). Although the dynamics of brain AP during the menstrual cycle have not been studied, it is likely that local synthesis of GABA A receptor-modulating neurosteroids occur in regions relevant to epilepsy such as the hippocampus and amygdala (Reddy, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the menstrual cycle, circulating progesterone levels are low in the follicular phase, but rise in the midluteal phase for approximately 10 to 11 days before declining in the late luteal phase. Circulating AP levels parallel those of its parent progesterone (Tuveri et al, 2008). Although the dynamics of brain AP during the menstrual cycle have not been studied, it is likely that local synthesis of GABA A receptor-modulating neurosteroids occur in regions relevant to epilepsy such as the hippocampus and amygdala (Reddy, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in ovarian hormones and modification of GABAergic inhibition are an intensely investigated hypothesis guiding research into pathophysiological mechanisms underlying catamenial epilepsy (Scharfman and MacLusky, 2006;Tuveri et al, 2008;Reddy, 2009). The main concern is the lack of a suitable mouse model to investigate the pathophysiological mechanisms of catamenial seizure exacerbations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed 300 nM AP to uncover the d-subunit-specific effects of neurosteroids on tonic conductance because d-containing GABA A Rs display greater sensitivity to neurosteroids at physiological or supraphysiological levels. Although the exact physiological levels of AP in the extracellular space within the hippocampus are unknown, the levels may range from 10 to 120 nM, depending on the physiological or other conditions such as estrous cycle or pregnancy (Murri and Galli, 1997;Bernardi et al, 1998a,b;Concas et al, 1998;Genazzani et al, 1998;Tuveri et al, 2008;Reddy, 2009). Even at low or physiological levels (30 nM), AP can elicit similar greater response in diestrus than in estrus per the standard linear concentration-response relationship (fractional response of maximal peak current).…”
Section: Neurosteroid Regulation Of Tonic Inhibition and Epileptogenesismentioning
confidence: 99%
“…These neurosteroids are increased in parallel to their precursor progesterone during the menstrual cycle (Tuveri et al, 2008). Progesterone and neurosteroids have anxiolytic, anticonvulsant, and neuroprotective properties (Reddy, 2004;Reddy et al, 2005) and have been shown to play a significant role in epilepsy, anxiety, and depression (Smith et al, 1998b;Reddy, 2003;van Broekhoven and Verkes, 2003;Reddy and Jian, 2010).…”
Section: Introductionmentioning
confidence: 99%